Academic Leadership of Quality School Administrators under Narathiwat Primary Educational Service Area Office 3 - มะมิง, อับดุลรอห์มัน (Al-HIKMAH Journal, 2021)
The objective of this research were (1) to study the level of academic leader ship of quality school administrators under Narathiwat primary education service area office 3 (2) to compare the level of academic leader ship of quality school administrators under Narathiwat primary education service area office 3 Classified by gender, position status, work experiences and school size (3) to process the problem and academic leader ship of school administrators under Narathiwat primary education service area office 3 The samples used in the study were 214 included school administrators and teachers under quality school of Narathiwat primary education service area 3 The research instruments was questionnaires The statistics used to analyze data world percentage,mean, standard deviation, t-test, F-test and The difference multiple compilations of Scheffe method The independent research results showed that 1) The level of academic leadership of quality school administrators was at the high-level. 2) The result of compression of academic leadership of quality school administrators classified by gender and school size on overall image and individual aspects are not different. The variable of work experience and position status award to academic leader ship of school Administrators was significantly different at .01 3) The academic leadership problems of school administrators of quality school found that the school administrators did not allow and opened minded for teachers and personnel to participate in relation of school visions, goals and mission for the school, moreover the school administrators were really open minded to under commissioned and lack of follow up on learning management system of teachers.